Method for manufacturing grain-oriented electrical steel sheet
Patent Information
- Application Number
- CN202280037045.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-28
- Filing Date
- 2022-05-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-05-26
AI Technical Summary
[0005]然而,在上述的加热方法中,由于是短时间的快速加热,因此存在如下的问题:容易产生因板坯内的位置导致的加热不均,加热温度变得不均匀,或者抑制剂形成成分等容易发生微观偏析的成分的均匀分散变得不充分,产品的磁特性在卷材的宽度方向、长度方向上发生变动
[0045] According to the present invention, it is possible to manufacture oriented electromagnetic steel sheets with high magnetic flux density and low iron loss inexpensively with high yield.
Smart Images

Figure CN117460851B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a so-called oriented electromagnetic steel sheet in which the grain Miller index is highly concentrated on the plate surface {110} and highly concentrated in the rolling direction <001>. Background Technology
[0002] Oriented magnetic steel sheets are soft magnetic materials, widely used primarily as cores in electrical equipment such as transformers. These sheets are produced through secondary recrystallization, resulting in a high concentration of grains in the {110}<001> orientation (hereinafter referred to as "Gaussian orientation"), thus endowing them with excellent magnetic properties such as low iron loss and high magnetic flux density. It should be noted that the magnetic properties of oriented magnetic steel sheets are typically evaluated using the magnetic flux density B8(T) at a magnetic field strength of 800 (A / m) and the iron loss W in a 1 kg sheet magnetized to 1.7 (T) under an AC magnetic field with an excitation frequency of 50 (Hz). 17 / 50 (W / kg)
[0003] As a method for manufacturing the aforementioned grain-oriented electromagnetic steel sheet, a common approach is to induce the precipitation of fine precipitates, known as inhibitors, during the final annealing process, thereby imparting a mobility difference to the grain boundaries and preferentially promoting the growth of only Gaussian-oriented grains. For example, Patent Document 1 discloses a method using AlN and MnS as inhibitors, and Patent Document 2 discloses a method using MnS and MnSe as inhibitors, both of which have been industrially applied. Ideally, these methods using inhibitors aim to achieve a uniform and finely dispersed inhibitor, which requires heating the steel billet, used as a raw material, to a high temperature of 1300°C or higher before hot rolling.
[0004] On the other hand, if the slab is heated at a high temperature for a prolonged period, the crystalline structure of the slab becomes coarse, leading to problems such as uneven microstructure. To address this issue, methods that heat the slab to a high temperature of approximately 1300–1450°C for a short period of time, as disclosed in Patent Document 3, have gradually become mainstream. Among the aforementioned slab heating methods are induction heating and electrothermal heating, as disclosed in Patent Documents 4 and 5. By applying this technology, not only can the coarsening of the crystalline structure be suppressed, but the slab can also be processed individually, thus increasing the flexibility in the timing of hot rolling. Furthermore, it is advantageous in terms of production efficiency and even in terms of equipment construction costs and maintenance and management costs.
[0005] However, the above heating method has the following problems due to the short-term rapid heating: uneven heating is easily caused by the position of the blank, the heating temperature becomes uneven, or the uniform dispersion of components that are prone to micro-segregation, such as inhibitors, becomes insufficient, and the magnetic properties of the product change in the width and length directions of the roll.
[0006] However, in addition to improving the aforementioned deviations in magnetic properties, there is a strong desire to supply oriented electromagnetic steel sheets at a low cost. Therefore, achieving a high yield rate for such high-quality products has become an important challenge for manufacturers. One issue that can be addressed in improving yield is preventing edge cracking at the edges of the steel sheet during hot rolling.
[0007] Various techniques have been proposed to prevent edge cracking during hot rolling. For example, Patent Document 6 discloses a method in which the temperature difference between the start and end temperatures of finishing rolling (i.e., the temperature reduction during finishing rolling) is set to below 220°C in the hot rolling process of continuously cast sheets for unidirectional silicon steel plates. However, even if the temperature difference between the start and end temperatures of finishing rolling is limited to such a range, it is impossible to prevent edge cracking that occurs in the early stages of finishing rolling during rough rolling.
[0008] Furthermore, Patent Documents 7-11 disclose hot rolling methods for oriented silicon steel that prevent edge cracking by adjusting the shape of the side surface of the sheet during hot rolling. Patent Document 12 proposes a method for limiting the final reduction rate in hot rough rolling; Patent Document 13 proposes a method for performing widening rolling and horizontal rolling after slab heating; Patent Document 14 proposes a method for controlling the casting structure of the slab; and Patent Document 15 proposes a method for making the cross-sectional shape of the slab a special shape.
[0009] Existing technical documents
[0010] Patent documents
[0011] Patent Document 1: Japanese Patent Publication No. 40-015644
[0012] Patent Document 2: Japanese Patent Publication No. 51-013469
[0013] Patent Document 3: Japanese Patent Application Publication No. 60-190520
[0014] Patent Document 4: Japanese Published Patent No. 58-024397
[0015] Patent Document 5: Japanese Patent Application Publication No. 60-145318
[0016] Patent Document 6: Japanese Patent Application Publication No. 55-062124
[0017] Patent Document 7: Japanese Patent Application Publication No. 60-145204
[0018] Patent Document 8: Japanese Patent Application Publication No. 60-200916
[0019] Patent Document 9: Japanese Patent Application Publication No. 61-071104
[0020] Patent Document 10: Japanese Patent Application Publication No. 62-196328
[0021] Patent Document 11: Japanese Patent Application Publication No. 05-138207
[0022] Patent Document 12: Japanese Patent Application Publication No. 54-031024
[0023] Patent Document 13: Japanese Patent Application Publication No. 03-133501
[0024] Patent Document 14: Japanese Patent Application Publication No. 03-243244
[0025] Patent Document 15: Japanese Patent Application Publication No. 61-003837 Summary of the Invention
[0026] However, in the technologies proposed in Patent Documents 7-11, when the shape of the slab side is poor, uneven depressions are generated at the grain boundaries of the coarsely grown crystals due to high-temperature heating, which become the starting point of edge cracks. Based on this understanding, widening rolling is performed on the entrance side of the finishing mill to adjust the shape of the side and prevent edge cracks. Compared with the method of widening rolling on the exit side of the finishing mill, the above method has a better effect in preventing edge cracks, but it has not yet achieved complete prevention of edge cracks. In addition, the technologies proposed in Patent Documents 12-15 also have some effect on edge cracks, but they still cannot be said to be effective methods that can completely prevent edge cracks.
[0027] The present invention was made in view of the above-mentioned problems existing in the prior art, and its object is to provide a technique that can effectively prevent edge cracks generated during hot rolling in a method for manufacturing oriented electromagnetic steel sheets using AlN, MnS and / or MnSe as inhibitors.
[0028] As a countermeasure to solve the aforementioned problems, the inventors conducted in-depth research focusing on the causes of edge cracking. Their results showed that edge cracking mostly occurs during the roughing stage of hot rolling. The main cause of edge cracking is the formation of a low-melting-point phase by sulfur (S), resulting in a localized liquid phase. Therefore, to prevent the aforementioned edge cracking, it is effective to appropriately manage the slab surface temperature from heating to the start of hot roughing, based on the S content of the slab, and to begin hot roughing at an appropriate slab side temperature. This led to the completion of the present invention.
[0029] Based on the above insights, the present invention provides a method for manufacturing an orientation-oriented electromagnetic steel sheet, characterized in that, in the method for manufacturing the orientation-oriented electromagnetic steel sheet, a material containing C: 0.02-0.10 wt%, Si: 2.5-5.5 wt%, Mn: 0.01-0.30 wt%, S: 0.0010-0.040 wt%, Se: 0-0.040 wt%, sol.Al: 0.010-0.040 wt%, and N: 0.004-0.020 wt%, with the remainder being Fe, is used. After heating the steel billet, which is composed of components including unavoidable impurities, it is hot rolled, and after hot rolling annealing or without hot rolling annealing, it is cold rolled once or twice or more with intermediate annealing to produce a cold rolled plate of the final thickness. It is then subjected to a recrystallization anneal that also serves as decarburization annealing. After applying an annealing separating agent to the surface of the steel plate, it is finally annealed. The heating temperature of the billet is set to 1300°C or higher, and the side temperature T of the billet at the beginning of the rough rolling of the hot rolling is set to the temperature T defined by the following formula (1). e The following widening rolling is performed after at least one pass of roughing rolling;
[0030] T e = -120000 [%S] 2 +1400……(1)
[0031] Here, [%S]: S content (mass%) of the slab.
[0032] The slab heating method of the above-mentioned oriented electromagnetic steel sheet manufacturing method of the present invention is characterized in that the slab surface temperature is heated to 1100 to 1300°C, held at the above temperature for 0 to 300 minutes, cooled down in the range of 50 to 200°C, and then the slab surface temperature is heated to 1300°C or higher at a heating rate of 100°C / hr or higher, and held at the above temperature for 0 to 180 minutes.
[0033] Furthermore, the manufacturing method of the above-mentioned orientation-oriented electromagnetic steel sheet of the present invention is characterized by comprising the following steps:
[0034] • Hot rolling process: The steel billet is heated to above 1100℃ and the above-mentioned T e After rough rolling for one or more passes in the following temperature range, hot-rolled plates are produced by finishing rolling for two or more passes in the temperature range of 800 to 1300°C. Then, they are wound into coils at a winding temperature of 400 to 750°C.
[0035] • Hot-rolled sheet annealing process: When annealing hot-rolled sheet, hold it in the temperature range of 800 to 1250°C for more than 5 seconds, and then cool it from 800°C to 350°C at a rate of 5 to 100°C / s.
[0036] • In the cold rolling process, the total reduction rate is in the range of 50% to 92% when cold rolling is performed once, and the total reduction rate of the final cold rolling to the final plate thickness is in the range of 50% to 92% when cold rolling is performed twice or more.
[0037] • Intermediate annealing process: In the case of intermediate annealing, after holding in the temperature range of 800 to 1250°C for more than 5 seconds, cool from 800°C to 350°C at a rate of 5 to 100°C / s.
[0038] • This process also serves as a primary recrystallization annealing step for decarburization annealing. The decarburization annealing is carried out in a humid atmosphere containing H2 and N2 with a dew point of 20–80°C for at least 10 seconds in a temperature range of 750–950°C.
[0039] • Annealing release agent coating process, with a single-sided application rate of 3g / m² on the steel plate surface. 2 The above coating is an annealing separating agent with MgO as the main component;
[0040] The final annealing process includes purification treatment at a temperature of at least 1050–1300°C for at least 3 hours, and a portion of the atmosphere in the temperature range above 800°C is an atmosphere containing H2.
[0041] Furthermore, the steel billet used in the manufacturing method of the oriented electromagnetic steel sheet of the present invention is characterized in that, in addition to the above-mentioned composition, it also contains at least one of the following: Ni: 0-1.00 wt%, Sb: 0-0.50 wt%, Sn: 0-0.50 wt%, Cu: 0-0.50 wt%, Cr: 0-0.50 wt%, P: 0-0.50 wt%, Mo: 0-0.50 wt%, Nb: 0-0.020 wt%, V: 0-0.010 wt%, B: 0-0.0025 wt%, Bi: 0-0.50 wt%, and Zr: 0-0.10 wt%.
[0042] Furthermore, the steel billet used in the above-described method for manufacturing the oriented electromagnetic steel sheet of the present invention is characterized in that, in addition to the above-described composition, it contains at least one component selected from Co: 0 to 0.0500% by mass and Pb: 0 to 0.0100% by mass.
[0043] Furthermore, the steel billet used in the above-described method for manufacturing the oriented electromagnetic steel sheet of the present invention is characterized in that, in addition to the above-described composition, it also contains at least one component selected from As: 0 to 0.0200 wt%, Zn: 0 to 0.0200 wt%, W: 0 to 0.0100 wt%, Ge: 0 to 0.0050 wt%, and Ga: 0 to 0.0050 wt%.
[0044] Invention Effects
[0045] According to the present invention, it is possible to manufacture oriented electromagnetic steel sheets with high magnetic flux density and low iron loss inexpensively with high yield. Attached Figure Description
[0046] Figure 1 This is a coordinate graph showing the influence of sulfur content in steel billets and the slab side temperature at the start of hot rough rolling on the size of edge cracks at the edge of hot-rolled plates. Detailed Implementation
[0047] First, the experiments used to develop this invention will be described.
[0048] <Experiment 1>
[0049] As shown in Table 1, four 260 mm thick steel slabs were manufactured, each with the following composition: C: 0.05–0.07 wt%, Si: 3.4–3.5 wt%, Mn: 0.07–0.08 wt%, sol.Al: 0.020–0.022 wt%, N: 0.007–0.008 wt%, Se: 0–0.027 wt%, with S varying to six levels within the range of 0.0005–0.036 wt%. The remainder consisted of Fe and unavoidable impurities. The slabs were heated in an electrically heated furnace until the surface temperature reached 1420 °C. The slabs were then removed and air-cooled until the side surface temperature reached the temperature T shown in Table 1. Hot rough rolling was then initiated. The rough rolling was performed in four passes to produce 40 mm thick sheets. It should be noted that in the rough rolling process described above, the sides of the rolled material are widened by reductions of 30 mm, 10 mm, 5 mm, and 2 mm after each pass. Then, hot finishing rolling begins at a surface temperature of 1100°C. After six passes, a hot-rolled plate with a thickness of 2.2 mm is produced, which is then water-cooled and wound into coils at a temperature of 600°C.
[0050] Next, continuous online photographs were taken at the exit side of the hot finishing mill. The maximum depth of edge cracks generated at the edge of the hot-rolled plate was determined from the obtained images, and the results are shown in Table 1. Additionally, Figure 1 The figure shows the effect of the sulfur content in the billet and the slab side temperature T at the start of rough rolling on the size of the aforementioned edge cracks. Based on these results, it can be seen that the slab side temperature T, in relation to the sulfur content, is defined by the following equation (1). e By starting rough rolling at the following temperature, the edge crack depth of the hot-rolled plate can be reduced to less than 10 mm.
[0051] T e = -120000 [%S] 2 +1400……(1)
[0052] Here, [%S]: S content (mass%) of the slab.
[0053] [Table 1]
[0054]
[0055] As mentioned above, the slab side temperature at the start of rough rolling is controlled according to the sulfur content in the billet. That is, for billets with a high sulfur content, the edge cracking of hot-rolled plates can be reduced by lowering the slab side temperature at the start of rough rolling. The inventors considered the following reasons.
[0056] When a slab is heated to a high temperature, even if the slab as a whole does not melt, in areas where sulfur is abundant, sulfur forms a low-melting-point phase, locally generating a liquid phase. If rough rolling is performed in this locally liquid phase state, a large difference in deformation capacity occurs at the solid-liquid interface, resulting in large edge cracks. Therefore, to suppress edge cracks, the slab side temperature needs to be pre-set to a temperature lower than the liquid phase emergence temperature at the start of rough rolling. Furthermore, the liquid phase emergence temperature decreases as the sulfur content in the steel billet increases; therefore, for billets with a high sulfur content, the slab side temperature needs to be further reduced at the start of rough rolling.
[0057] Next, oriented electromagnetic steel sheets were produced using the various hot-rolled sheets obtained as described above, and the magnetic properties of the product sheets were evaluated. Specifically, the hot-rolled sheets were annealed by holding them at 1100°C for 60 seconds, then water-cooled from 800°C to 350°C at 50°C / s, followed by pickling to remove the oxide scale from the steel sheet surface. Then, a cold-rolled sheet with a final thickness of 0.27 mm was produced by a single cold rolling process. This cold-rolled sheet was then subjected to a recrystallization annealing process at 820°C for 120 seconds in a humid atmosphere containing H2 and N2 with a dew point of 55°C, which also served as a decarburization annealing. Next, an annealing separating agent with MgO as the main component was applied to the steel sheet surface at a concentration of 5 g / m² on one side. 2 The coating is applied at a unit area weight and dried. Then, after secondary recrystallization, a final annealing process is performed, holding the coating at 1200°C for 20 hours for purification. During this process, the temperature range above 850°C is in an atmosphere dominated by H2. Next, unreacted annealing separating agent is removed from the surface of the final annealed steel sheet, followed by a phosphate-based insulating tension film. A planarization annealing process, which also serves as sintering of the film and shape correction of the steel sheet, is then performed to produce the product sheet.
[0058] Test pieces for magnetic property measurement were collected from the innermost and outermost coils of the product sheet obtained in this way. The magnetic flux density B8 at a magnetization of 800 A / m was measured using the method of JIS C 2550-1 (2011). The lowest value of magnetic flux density within one coil was taken as the guaranteed value within the coil, and the results are marked in Table 1. The results show that in order to obtain a good magnetic flux density of B8 ≥ 1.90 T, the sulfur content in the steel billet needs to be above 0.0010% by mass.
[0059] <Experiment 2>
[0060] Ten steel billets, each 220 mm thick, were manufactured. These billets contained C: 0.06 wt%, Si: 3.1 wt%, Mn: 0.09 wt%, S: 0.009 wt%, Se: 0.015 wt%, sol.Al: 0.020 wt%, and N: 0.007 wt%, with the remainder consisting of Fe and unavoidable impurities. The billets were heated in a gas-fired furnace until the surface temperature reached the holding temperature 1 shown in Table 2. After holding at this temperature for 20 minutes, the billets were removed from the gas-fired furnace and air-cooled until the surface temperature reached the temperature drop shown in Table 2. Next, the slab is placed in an induction heating furnace and heated to the holding temperature 2 shown in Table 2 at a heating rate of 100°C / hour. After holding at this temperature for 30 minutes, the slab is removed from the induction heating furnace and air-cooled until the side surface temperature reaches 1350–1280°C before rough rolling begins. Rough rolling is performed in three passes to produce a sheet with a thickness of 30 mm. At this time, the sides of the rolled material are widened by reductions of 10 mm, 6 mm, and 2 mm after each pass. Then, finish rolling begins when the surface temperature of the rolled material (sheet) is 1200°C. After six passes, a hot-rolled sheet with a thickness of 2.8 mm is produced, which is then water-cooled and wound into a coil at 500°C. Next, photographs were continuously taken online at the exit side of the hot finishing mill, and the maximum depth of the edge cracks generated at the edge of the hot-rolled plate was determined from the obtained images. The results are shown in Table 2.
[0061] [Table 2]
[0062]
[0063] T calculated from the steel composition of the above slab e The slab side temperature T at the start of rough rolling is 1390℃, and all slab side temperatures T satisfy T≤T. eDue to the conditions, the maximum edge crack depth of all hot-rolled plates was less than 10 mm. However, in the hot-rolled plates that were heated to 1100–1300°C using a slab surface thermometer, then temporarily cooled by 50–200°C (measured by the decrease in slab surface temperature), and then reheated to 1380°C before rough rolling, the maximum edge crack depth was less than 5 mm, demonstrating a significant edge crack prevention effect.
[0064] The reasons are not yet fully clear, but the inventors believe they are as follows: In slab heating using combustion gas, the slab surface is easily heated while the center is difficult to heat, resulting in a large temperature difference within the slab. Slabs heated to temperatures above 1300°C under these large temperature differences are above the temperature at which a liquid phase appears locally at the start of rough rolling, thus causing some edge cracks. On the other hand, in slabs heated to 1100–1300°C using a slab surface thermometer, then temporarily cooled by 50–200°C (measured by the decrease in surface temperature), and then heated again to 1380°C using the same thermometer, a large temperature difference is generated within the slab during the first heating phase. However, during the cooling phase, the temperature distribution within the slab becomes uniform, and this uniformity is maintained even after the second heating phase. Therefore, the slab side temperature at the start of rough rolling is below the temperature at which a liquid phase appears, resulting in significantly suppressed edge cracks.
[0065] Next, oriented electromagnetic steel sheets were manufactured using the hot-rolled sheet obtained as described above, and the magnetic properties of the product sheets were evaluated. Specifically, the hot-rolled sheet was pickled to remove the oxide scale from the steel sheet surface, and then subjected to a first cold rolling to produce an intermediate sheet thickness of 1.5 mm. After holding at 1050°C for 30 seconds, it underwent intermediate annealing by water cooling from 800°C to 350°C at 80°C / s, followed by pickling, and then a second cold rolling to produce a cold-rolled sheet with a final sheet thickness of 0.23 mm. Next, the cold-rolled sheet was subjected to a first recrystallization annealing at 840°C for 100 seconds in a humid atmosphere containing H2 and N2 with a dew point of 60°C, which also served as a decarburization annealing. Finally, an annealing separating agent with MgO as the main component was applied to the steel sheet surface at a concentration of 8 g / m² on one side. 2 The coating is applied per unit area weight and dried. Then, after secondary recrystallization, a final annealing process is performed, holding the coating at 1180°C for 5 hours for purification. During this process, an atmosphere primarily composed of H2 is used in the temperature range above 1100°C. Next, unreacted annealing separating agent is removed from the surface of the final annealed steel sheet. A phosphate-based insulating tension film is then applied, followed by planarization annealing, which serves both as sintering of the film and shape correction of the steel sheet, to produce the finished product sheet.
[0066] Test pieces for magnetic property measurement were collected from the innermost and outermost coils of the product sheet obtained in this way. The magnetic flux density B8 at a magnetization of 800 A / m was measured using the method described in JIS C 2550-1 (2011). The lowest magnetic flux density within a single coil was taken as the guaranteed value within the coil, and the results are listed in Table 2. The results show that the steel sheets manufactured under the conditions of this invention all achieved a good magnetic flux density of B8 ≥ 1.90 T.
[0067] Next, the composition of the steel billet (slab) used in the manufacture of the oriented electromagnetic steel sheet of the present invention will be described.
[0068] C: 0.02–0.10% by mass
[0069] Carbon (C) is a necessary component for improving the microstructure of hot-rolled steel sheets by utilizing the austenite-ferrite phase transformation that occurs during hot rolling and homogenization during annealing. However, if the C content is less than 0.02% by mass, the grain boundary strengthening effect provided by C is lost, leading to defects such as cracking in the slab that hinder manufacturing. On the other hand, when the C content exceeds 0.10% by mass, not only does the load on the decarburization annealing process increase, but decarburization itself becomes incomplete, resulting in magnetic aging of the product sheet and deterioration of magnetic properties. Therefore, the C content is set in the range of 0.02 to 0.10% by mass, preferably in the range of 0.03 to 0.08% by mass.
[0070] Si: 2.5–5.5% by mass
[0071] Si is an extremely effective component for increasing the resistivity of steel and thus reducing eddy current losses, which constitute part of iron loss. However, when the Si content is less than 2.5% by mass, the aforementioned reduction effect is small, and good iron loss characteristics cannot be obtained. On the other hand, the resistivity of steel increases monotonically up to 11% by mass, but if it exceeds 5.5% by mass, the workability decreases significantly, making it difficult to roll and manufacture. Therefore, the Si content is set in the range of 2.5 to 5.5% by mass, preferably in the range of 3.0 to 4.0% by mass.
[0072] Mn: 0.01~0.30% by mass
[0073] Mn forms MnS and MnSe, which function as inhibitors of normal grain growth during the final annealing heating process, making it an important component in the manufacture of grain-oriented electromagnetic steel sheets. However, if the Mn content is less than 0.01% by mass, the absolute amount of inhibitor is insufficient, and the inhibitory effect on normal grain growth becomes inadequate. On the other hand, if the Mn content exceeds 0.30% by mass, it is difficult to achieve sufficient solidification during slab heating, and the magnetic properties may deteriorate. Therefore, the Mn content is set in the range of 0.01 to 0.30% by mass, preferably in the range of 0.05 to 0.20% by mass.
[0074] S: 0.0010~0.040% by mass
[0075] S combines with Mn to form MnS, which acts as an inhibitor. However, when the content is less than 0.0010% by mass, the inhibitory amount is insufficient, and the improvement in magnetic properties cannot be fully achieved. On the other hand, when the content exceeds 0.040% by mass, it is difficult to achieve sufficient solidification by heating the slab, and the magnetic properties may deteriorate significantly. In addition, if the content exceeds 0.040% by mass, edge cracks will occur during hot rolling. Therefore, in order to achieve both magnetic properties and manufacturability, the S content is set in the range of 0.0010 to 0.040% by mass. Preferably, it is in the range of 0.0020 to 0.015% by mass.
[0076] Se: 0–0.040% by mass
[0077] Se, like S, combines with Mn to form MnSe, which acts as an inhibitor. However, if the content exceeds 0.040% by mass, it cannot be fully dissolved by heating the slab, resulting in a significant deterioration of the magnetic properties. Therefore, the Se content is set in the range of 0 to 0.040% by mass, preferably in the range of 0.005 to 0.020% by mass.
[0078] sol.Al: 0.010–0.040% by mass
[0079] Al is an important component in oriented electromagnetic steel sheets, precipitating as AlN and functioning as an inhibitor of normal grain growth during secondary recrystallization annealing. However, when the Al content, calculated as acid-soluble Al (sol.Al), is less than 0.010% by mass, the absolute amount of inhibitor is insufficient, resulting in inadequate inhibition of normal grain growth. On the other hand, when the Al content, calculated as sol.Al, exceeds 0.040% by mass, it cannot be sufficiently dissolved in the steel during slab heating, failing to achieve fine dispersion within the steel, leading to a significant deterioration in magnetic properties. Therefore, the Al content, calculated as sol.Al, is set in the range of 0.010 to 0.040% by mass, preferably in the range of 0.015 to 0.030% by mass.
[0080] N: 0.004–0.020% by mass
[0081] Nitrogen (N) is a component that combines with Al and precipitates to form AlN, which acts as an inhibitor. However, when the content is less than 0.004% by mass, the absolute amount of inhibitor is insufficient, resulting in insufficient inhibition of normal grain growth. On the other hand, when the content exceeds 0.020% by mass, the slab may expand during hot rolling. Therefore, the N content is set in the range of 0.004 to 0.020% by mass, preferably in the range of 0.006 to 0.010% by mass.
[0082] In addition to the essential components mentioned above, the steel billet used in this invention may contain at least one component selected from Ni: 0-1.00 wt%, Sb: 0-0.50 wt%, Sn: 0-0.50 wt%, Cu: 0-0.50 wt%, Cr: 0-0.50 wt%, P: 0-0.50 wt%, Mo: 0-0.50 wt%, Nb: 0-0.020 wt%, V: 0-0.010 wt%, B: 0-0.0025 wt%, Bi: 0-0.50 wt%, and Zr: 0-0.10 wt% in order to improve magnetic properties. If the content of any component exceeds the above-mentioned upper limit, the development of secondary recrystallization is suppressed, which in turn deteriorates the magnetic properties. Furthermore, from the viewpoint of reliably improving magnetic properties, it is preferable to add Ni: 0.01% by mass or more, Sb: 0.005% by mass or more, Sn: 0.005% by mass or more, Cu: 0.01% by mass or more, Cr: 0.01% by mass or more, P: 0.005% by mass or more, Mo: 0.005% by mass or more, Nb: 0.001% by mass or more, V: 0.001% by mass or more, B: 0.0002% by mass or more, Bi: 0.005% by mass or more, and Zr: 0.001% by mass or more.
[0083] In addition to the above-mentioned composition, the steel billet used in this invention may also contain at least one component selected from Co: 0 to 0.0500 wt% and Pb: 0 to 0.0100 wt% to improve magnetic properties. If the content of each component exceeds the above-mentioned upper limit, the development of secondary recrystallization is suppressed, which in turn deteriorates the magnetic properties. Furthermore, from the viewpoint of reliably improving magnetic properties, it is preferable to add Co: 0.0020 wt% or more and Pb: 0.0001 wt% or more.
[0084] In addition to the above-mentioned composition, the steel billet used in this invention may also contain at least one component selected from As: 0-0.0200 wt%, Zn: 0-0.0200 wt%, W: 0-0.0100 wt%, Ge: 0-0.0050 wt%, and Ga: 0-0.0050 wt% for the purpose of improving magnetic properties. If the content of each component exceeds the above-mentioned upper limit, the development of secondary recrystallization is suppressed, which in turn deteriorates the magnetic properties. It should be noted that, from the viewpoint of reliably improving magnetic properties, it is preferable to add As: 0.0010 wt% or more, Zn: 0.0010 wt% or more, W: 0.0010 wt% or more, Ge: 0.0001 wt% or more, and Ga: 0.0001 wt% or more.
[0085] It should be noted that Ti forms nitrides, which are detrimental to the inhibitory effect of AlN and should be minimized as much as possible. However, reducing Ti increases refining costs, but this is permissible if it is below 0.010% by mass. More preferably, the content is below 0.0020% by mass.
[0086] It should be noted that the steel billet used in this invention contains, in addition to the components mentioned above, Fe and unavoidable impurities. Here, unavoidable impurities refer to components that inevitably mix in during steel smelting from raw materials, scrap, smelting pots, etc.
[0087] Next, the manufacturing method of the oriented electromagnetic steel sheet of the present invention will be described.
[0088] The steel billet (slab) used in the manufacture of the oriented electromagnetic steel sheet of the present invention can be made by melting steel with the above-mentioned composition through a commonly known refining process and then by using a commonly known ingot casting method or continuous casting method, or by using a direct casting method to manufacture thin casting sheets with a thickness of less than 100 mm.
[0089] The aforementioned slabs and thin castings are heated using conventional methods and then supplied for hot rolling. The slab heating temperature before hot rolling is preferably set to above 1300°C to ensure that the inhibitory components are completely dissolved in the steel. The slab can be heated to above 1300°C using a single furnace, or it can be heated using two or more furnaces. Known methods for heating the slab include combustion gas heating, electric heating, and induction heating.
[0090] Furthermore, one of the most significant features of this invention is that, in the aforementioned slab heating process, after heating and holding the slab surface temperature to 1100°C to 1300°C, it is cooled within a range of 50 to 200°C, based on the decrease in slab surface temperature. Then, it is heated again at a heating rate of 100°C / hr or higher until the slab surface temperature reaches 1300°C or higher, and held at this temperature for 0 to 180 minutes. The reason for setting the heating rate during reheating to 100°C / hr or higher is to avoid the formation of a ferrite-austenite two-phase structure in the temperature range below 1300°C, which would cause volume changes and result in shape defects in the sliding portion of the slab support. Additionally, the slab can be cooled using known methods such as air cooling, gas cooling, water cooling, or contact cooling using rollers, etc.
[0091] After heating the slab to above 1300°C using a surface thermometer as described above, it is cooled, and the surface temperature of the rolled material is above 1100°C and T e Sheets are produced by rough rolling in the following temperature range for one or more passes. At this time, by performing widening rolling after at least one pass of rough rolling, edge cracking can be suppressed. The widening rolling can be performed using known methods such as vertical rolls, and the reduction amount of the widening rolling is preferably set in the range of 1 to 50 mm. More preferably, it is in the range of 5 to 30 mm. It should be noted that the reduction amount mentioned above in this invention is a value per side.
[0092] In addition, another major feature of the present invention is that the side surface temperature T of the slab as the rolled material is a temperature T defined by the following formula (1). e Hot roughing begins at the following temperatures. It should be noted that the slab side temperature T refers to the highest temperature measured along the entire length of the slab side.
[0093] T e = -120000 [%S] 2 +1400……(1)
[0094] Wherein, [%S]: S content (mass %) of the slab.
[0095] To improve the microstructure of the hot-rolled sheet, the finishing rolling following the rough rolling is preferably carried out in two or more passes at a surface temperature of 800–1300°C. Furthermore, from the viewpoint of controlling carbide microstructure and preventing defects such as cracking, the winding temperature of the finished coil is preferably set to a range of 400–750°C. More preferably, it is set to a range of 500–700°C.
[0096] From the viewpoint of homogenizing the microstructure of the steel sheet and reducing deviations in magnetic properties, the hot-rolled steel sheet (hot-rolled plate) is preferably subjected to hot-rolled annealing at a temperature of 800–1250°C for at least 5 seconds. More preferably, it is subjected to annealing at a temperature of 900–1150°C for 10–180 seconds. Furthermore, from the viewpoint of controlling the morphology of the second phase and precipitates, the cooling after the heat treatment is preferably performed in a temperature range of 800°C–350°C at a cooling rate of 5–100°C / s. More preferably, the cooling rate is in the range of 15–80°C / s.
[0097] Next, in order to remove the oxide film generated on the surface of the steel plate during hot rolling, the steel plate (hot-rolled plate) after hot rolling or annealing is preferably descaled. The descaled method can be a known method such as pickling with heated acid, mechanical descaled method to remove oxide scale, or a combination of these methods.
[0098] A cold-rolled sheet of final thickness is produced by cold rolling a hot-rolled sheet with the oxide scale removed in one pass or by cold rolling two or more passes with intermediate annealing. When performing the intermediate annealing, it is preferable to hold the sheet at a temperature of 800–1250°C for at least 5 seconds. Below 800°C, the recrystallization grains become too fine, reducing the number of Goss nuclei in the primary recrystallization structure, potentially leading to deterioration of magnetic properties. On the other hand, if the temperature exceeds 1250°C, rapid growth and decomposition of inhibitors occur, which may still lead to deterioration of magnetic properties. More preferably, the sheet is held at a temperature of 900–1150°C for 10–180 seconds.
[0099] From the viewpoint of controlling the morphology of the second phase and precipitates, the cooling after the above heat treatment is preferably performed at a rate of 5 to 100 °C / s from 800 °C to 350 °C. A more preferred cooling rate is in the range of 15 to 80 °C / s. It should be noted that, in the case of intermediate annealing, it is preferable to remove the rolling oil beforehand. In addition, after intermediate annealing, it is preferable to remove the oxide scale generated on the surface of the steel sheet during annealing. The oxide scale removal method can employ known methods such as pickling with heated acid, mechanical descaling methods that mechanically remove oxide scale, or a combination of these methods.
[0100] Furthermore, in cold rolling, lubricants such as rolling oil are preferably used to reduce rolling load and improve the shape of the rolled steel sheet. Also, from the viewpoint of microstructure control, when the final sheet thickness is achieved through a single cold rolling operation, it is preferable to set the total reduction rate of the cold rolling process to a range of 50% to 92%. On the other hand, when performing two or more cold rolling operations, it is preferable to set the total reduction rate of the final cold rolling process to achieve the final sheet thickness to a range of 50% to 92%.
[0101] After cold rolling to the final sheet thickness (cold-rolled sheet), a primary recrystallization annealing, which also serves as a decarburization annealing, is performed. However, it is preferable to pre-clean the steel sheet surface by degreasing and pickling beforehand. The decarburization annealing conditions in the primary recrystallization annealing are preferably maintained at a temperature of 750–950°C for at least 10 seconds. More preferably, the conditions are in the range of 800–900°C for 30–180 seconds. In addition, the atmosphere during the above-mentioned decarburization annealing is preferably set to a humid atmosphere consisting of H2 and N2 with a dew point of 20–80°C. More preferably, the dew point is in the range of 40–70°C. By performing the above-mentioned decarburization annealing, the carbon content in the steel is reduced to below 0.0050% by mass, making magnetic aging difficult.
[0102] The steel sheet after the above-mentioned recrystallization annealing is preferably subjected to a single-sided center thickness of 3 g / m. 2 The above figure represents the amount of annealing release agent with MgO as the main component coated per unit area. There is no particular upper limit to the unit area weight, but from a manufacturing cost perspective, it is preferably set at 10 g / m². 2 It should be noted that MgO can be prepared as a slurry and coated onto the surface of a steel plate, or it can be dry-coated using electrostatic coating. When coating with a slurry, it is preferable to maintain the slurry solution at a temperature below 15°C to suppress the increase in slurry viscosity. Furthermore, to maintain a constant slurry concentration, it is preferable to manage the slurry solution separately in a mixing tank and a tank for coating. It should be noted that MgO as the main component means that the content of MgO relative to the total annealing separating agent is 60% by mass or more.
[0103] After the steel sheet coated with an annealing release agent is wound into a coil and placed in an upright position, final annealing is performed to promote secondary recrystallization and form a magnesium olivine coating on the surface of the steel sheet. At this time, in order to prevent the outer roll of the coil from unwinding, it is preferable to wrap a strip or similar material around the outer periphery of the coil.
[0104] To achieve secondary recrystallization, the final annealing is preferably performed at a temperature of 800°C or higher. Furthermore, to form a magnesium olivine film on the steel plate surface, heating to 1050°C or higher is preferred. Additionally, to remove inhibitor-forming components and impurities from the steel and obtain good magnetic properties, a purification treatment is preferably performed, maintaining the temperature at 1050–1300°C for at least 3 hours. By performing this purification treatment, inhibitor-forming components can be reduced to impurity levels. In this case, the atmosphere comprising a portion of the temperature range of 800°C or higher, including the purification treatment maintained at at least 1050–1300°C for at least 3 hours, is preferably set to an atmosphere containing H2.
[0105] For steel plates that have undergone the aforementioned final annealing, after removing the unreacted annealing separating agent through washing, brushing, pickling, etc., in order to correct the curling marks and shape defects of the steel plates generated during the final annealing and reduce iron loss, it is preferable to perform planarization annealing.
[0106] It should be noted that while oriented electromagnetic steel sheets are mostly used by stacking steel sheets, it is preferable to coat the steel sheet surface with an insulating film to ensure insulation. The insulating film is preferably of the tension-applied type, which has the effect of reducing iron loss. The coating of the insulating film on the steel sheet surface can be performed by applying a coating solution before planarization annealing and then sintering it through planarization annealing, or it can be done on other production lines. Furthermore, to improve the film adhesion and obtain a greater iron loss reduction effect, the film can also be applied under tension using an adhesive, or inorganic materials can be deposited onto the steel sheet surface using physical vapor deposition or chemical vapor deposition methods.
[0107] Furthermore, from the perspective of further reducing iron loss, magnetic domain refinement can be implemented in any process after cold rolling by etching to form grooves on the surface of the steel plate, or by irradiating the surface of the steel plate with heat energy beams such as lasers or plasma after forming an insulating film to form a thermal strain region, or by pressing a roller with protrusions onto the surface of the steel plate to form a processing strain region.
[0108] Example 1
[0109] As shown in Table 3, four steel billets with a thickness of 260 mm were manufactured. These billets had the following composition: C: 0.06–0.08 wt%, Si: 3.3–3.5 wt%, Mn: 0.08–0.10 wt%, Se: 0.016–0.020 wt%, sol.Al: 0.018–0.025 wt%, N: 0.007–0.009 wt%, and S was varied across four levels within the range of 0.0008–0.022 wt%. The remainder consisted of Fe and unavoidable impurities. The billets were then heated in a gas-fired furnace until the surface temperature reached the holding temperature 1 shown in Table 3. After holding at this temperature for 60 minutes, the billets were removed from the gas-fired furnace and air-cooled until the surface temperature reached the temperature drop shown in Table 3. Next, the slab was heated in an induction heating furnace at a heating rate of 200°C / hr until the surface temperature of the slab reached the holding temperature 2 shown in Table 3. After holding the slab at this temperature for 10 minutes, the slab was removed and air-cooled until the side temperature of the slab reached 1258–1294°C before hot roughing. The roughing was performed in 5 passes to produce a sheet with a thickness of 50 mm. At this point, after 3 and 5 passes, the sides of the rolled material were widened by reductions of 20 mm and 5 mm, respectively. Then, hot finishing rolling was started at a surface temperature of 1200°C, and after 6 passes, a hot-rolled sheet with a thickness of 2.6 mm was produced. After water cooling, it was wound into a coil at 500°C. At this point, continuous online photographs were taken at the exit side of the hot finishing mill, and the maximum depth of edge cracks generated at the edge of the hot-rolled sheet was determined from the obtained images. The results are shown in Table 3.
[0110]
[0111] The slab side temperature T at the start of rough rolling in the above example is relative to T calculated from the steel composition of each slab. e All satisfy T≤T e Due to these conditions, the maximum depth of edge cracks generated at the edge of hot-rolled coils is less than 10 mm. However, it is known that in hot-rolled plates where the slab is heated to 1200°C using a slab surface thermometer and held, then temporarily cooled within a range of 50–200°C (measured by the decrease in slab surface temperature), and then heated to 1420°C using a slab surface thermometer and held before rough rolling, the maximum depth of edge cracks is less than 5 mm, further reducing the severity of edge cracks.
[0112] Next, to evaluate the magnetic properties of the final product sheet, the hot-rolled sheet was subjected to hot-rolled annealing by holding it at 1000°C for 20 seconds and then water-cooling it from 800°C to 350°C at 10°C / s. Then, it was pickled to remove the surface oxide scale. Next, a first cold rolling was performed to produce an intermediate sheet with a thickness of 1.5 mm. After holding it at 1200°C for 30 seconds, it was water-cooled from 800°C to 350°C at 10°C / s for intermediate annealing. It was then pickled again and subjected to a second cold rolling to produce a final sheet with a thickness of 0.18 mm. Next, the cold-rolled sheet was subjected to a first recrystallization annealing at 900°C for 120 seconds in a humid atmosphere containing H2 and N2 with a dew point of 45°C, which also served as a decarburization annealing. Finally, an annealing separating agent mainly composed of MgO was applied at a concentration of 7 g / m² on one side. 2 The coating is applied to the surface of a steel sheet and dried. Then, after secondary recrystallization, a final annealing process is performed, holding the coating at 1150°C for 20 hours for purification. It should be noted that in this final annealing, the temperature range above 1000°C is set in an atmosphere primarily composed of H2. Next, after removing unreacted annealing separating agent from the surface of the steel sheet after final annealing, a phosphate-based insulating tension film is applied, followed by planarization annealing that combines film sintering and steel sheet shape correction to produce the finished product sheet.
[0113] Test pieces for magnetic property measurement were collected from the innermost and outermost rolls of the product sheet obtained in this way. The magnetic flux density B8 at a magnetization of 800 A / m was measured using the method described in JIS C 2550-1 (2011). The lowest magnetic flux density within a single roll was taken as the guaranteed value within the roll, and the results are recorded in Table 3. These results show that, using a slab blank with a composition suitable for the present invention, product sheets manufactured under the conditions satisfying the present invention all achieve a good magnetic flux density of B8 ≥ 1.90 T.
[0114] Example 2
[0115] A 220mm thick steel billet, containing all the components shown in Table 4, with the balance being Fe and unavoidable impurities, is heated in a gas-fired furnace to a surface temperature of 1100°C. After holding at this temperature for 30 minutes (heating step 1), the billet is removed from the gas-fired furnace and air-cooled until the surface temperature decreases by 100°C. It is then placed in an induction-heated furnace and heated to a surface temperature of 1420°C. After holding at this temperature for 30 minutes (heating step 2), the billet is removed and air-cooled until the side surface temperature reaches temperature T shown in Table 4. Hot roughing then begins. This roughing is performed in three passes to produce a 30mm thick sheet. It should be noted that after each pass, the sides of the rolled material are widened by reductions of 10mm, 5mm, and 2mm, respectively. Then, hot finishing rolling was started at a surface temperature of 1200°C, and a hot-rolled plate with a thickness of 2.6 mm was produced through 7 passes. After water cooling, it was wound into coils at a temperature of 600°C. For the hot-rolled plate thus obtained, online continuous photographs were taken on the exit side of the hot finishing mill. From the obtained images, the maximum depth of edge cracks generated at the edge of the steel plate was measured, and the results are shown in Table 4.
[0116]
[0117]
[0118] The hot-rolled plates listed in the table above all meet the requirement that the slab side temperature T at the start of hot roughing is relative to T calculated from the steel composition of the slab. e For T≤T e In addition, during slab heating, the following conditions are met: after heating and maintaining the slab surface temperature to 1100-1300°C, the slab surface temperature is temporarily cooled within a range of 50-200°C by the amount of temperature drop. Then, the slab surface temperature is heated to above 1300°C and maintained at this temperature before rough rolling begins. Therefore, the maximum depth of edge cracks generated at the edge of the hot-rolled plate is less than 5mm, which can significantly prevent edge cracks.
[0119] Next, to evaluate the magnetic properties of the final product sheet, the hot-rolled sheet was subjected to hot-rolled annealing at 1000°C for 60 seconds, followed by water cooling from 800°C to 350°C at 50°C / s, and then pickling to remove the surface oxide scale. Next, a first cold rolling was performed to produce an intermediate sheet with a thickness of 1.8 mm. After holding at 1100°C for 100 seconds, it was water-cooled from 800°C to 350°C at 70°C / s for intermediate annealing, followed by pickling again, and then a second cold rolling to produce a final sheet with a thickness of 0.23 mm. Next, the cold-rolled sheet was subjected to a first recrystallization annealing at 840°C for 120 seconds in a humid atmosphere containing H2 and N2 with a dew point of 60°C, which also served as a decarburization annealing. Finally, an annealing separating agent with MgO as the main component was applied at a concentration of 5 g / m² on one side. 2 The coating is applied to the surface of the steel sheet and dried. Then, after secondary recrystallization, a final annealing process is performed, holding the coating at 1200°C for 5 hours for purification. It should be noted that in the final annealing, the temperature range above 1050°C is set in an atmosphere primarily composed of H2. Next, after removing unreacted annealing separating agent from the surface of the final annealed steel sheet, a phosphate-based insulating tension film is applied, followed by planarization annealing that combines film sintering and steel sheet shape correction to produce the product sheet.
[0120] Test pieces for magnetic property measurement were collected from the innermost and outermost rolls of the product sheet obtained in this way. The magnetic flux density B8 at a magnetization of 800 A / m was measured using the method described in JIS C 2550-1 (2011). The lowest magnetic flux density within a single roll was taken as the guaranteed value within the roll, and the results are recorded in Table 4. The results show that, using a slab with a composition satisfying the present invention, the product sheets manufactured under the conditions satisfying the present invention all achieved a good magnetic flux density of B8 ≥ 1.90 T.
Claims
1. A method for manufacturing an orientation-oriented electromagnetic steel sheet, characterized in that, The process includes the following steps: A steel billet containing C: 0.02–0.10% by mass, Si: 2.5–5.5% by mass, Mn: 0.01–0.30% by mass, S: 0.0010–0.040% by mass, Se: 0–0.040% by mass, sol.Al: 0.010–0.040% by mass, and N: 0.004–0.020% by mass, with the remainder being Fe and unavoidable impurities, is heated, then hot-rolled, annealed (or not annealed), then cold-rolled once or twice or more with intermediate annealing to produce a cold-rolled sheet of the final thickness, then recrystallized annealing (which also serves as decarburization annealing), then an annealing separating agent is applied to the surface of the steel sheet, and finally annealed. The heating temperature of the steel billet is set to above 1300℃. The slab side temperature T at the start of the hot rolling roughing is set to the temperature T defined by the following equation (1). e the following, Furthermore, widening rolling is performed after at least one pass of roughing rolling. Wherein, [%S]: S content of the slab by mass%.
2. The method for manufacturing the oriented electromagnetic steel sheet according to claim 1, characterized in that, In the heating of the steel billet, the billet surface temperature is heated to 1100-1300°C. After holding the temperature at 1100-1300°C for 0-300 minutes, the billet surface temperature is cooled by a decrease of 50-200°C. Then, the billet surface temperature is heated to 1300°C or higher at a heating rate of 100°C / hr or higher, and held at 1300°C or higher for 0-180 minutes.
3. The method for manufacturing an orientation-oriented electromagnetic steel sheet according to claim 1 or 2, characterized in that, It has the following processes: Hot rolling process: The steel billet is heated to above 1100℃ and the T... e After rough rolling for one or more passes in the following temperature range, hot-rolled plates are produced by finishing rolling for two or more passes in the temperature range of 800 to 1300°C. Then, they are wound into coils at a winding temperature of 400 to 750°C. Hot-rolled sheet annealing process: When annealing hot-rolled sheet, it is held in the temperature range of 800 to 1250°C for more than 5 seconds, and then cooled from 800°C to 350°C at a rate of 5 to 100°C / s. Cold rolling process: When performing cold rolling once, the total reduction rate is in the range of 50% to 92%. When performing cold rolling twice or more, the total reduction rate of the final cold rolling to achieve the final plate thickness is in the range of 50% to 92%. Intermediate annealing process: When performing intermediate annealing, hold the temperature in the range of 800 to 1250°C for more than 5 seconds, and then cool from 800°C to 350°C at a rate of 5 to 100°C / second. The recrystallization annealing process, which also serves as decarburization annealing, involves holding the anneal at a temperature range of 750–950°C for more than 10 seconds in a humid atmosphere containing H2 and N2 with a dew point of 20–80°C. Annealing release agent coating process: Apply annealing release agent with an MgO content of 60% or more by mass to the surface of the steel plate at a rate of 3g / m² on one side. 2 Apply the coating as described above; Final annealing process: includes purification treatment at a temperature of at least 1050 to 1300°C for at least 3 hours, and a portion of the atmosphere in the temperature range above 800°C is an atmosphere containing H2.
4. The method for manufacturing an orientation-oriented electromagnetic steel sheet according to claim 1 or 2, characterized in that, In addition to the aforementioned composition, the steel billet also contains at least one component selected from the following: Ni: 0–1.00 wt%, Sb: 0–0.50 wt%, Sn: 0–0.50 wt%, Cu: 0–0.50 wt%, Cr: 0–0.50 wt%, P: 0–0.50 wt%, Mo: 0–0.50 wt%, Nb: 0–0.020 wt%, V: 0–0.010 wt%, B: 0–0.0025 wt%, Bi: 0–0.50 wt%, and Zr: 0–0.10 wt%.
5. The method for manufacturing an orientation-oriented electromagnetic steel sheet according to claim 1 or 2, characterized in that, In addition to the aforementioned composition, the steel billet also contains at least one component selected from Co: 0 to 0.0500% by mass and Pb: 0 to 0.0100% by mass.
6. The method for manufacturing an orientation-oriented electromagnetic steel sheet according to claim 1 or 2, characterized in that, In addition to the aforementioned composition, the steel billet also contains at least one component selected from the group consisting of As: 0–0.0200% by mass, Zn: 0–0.0200% by mass, W: 0–0.0100% by mass, Ge: 0–0.0050% by mass, and Ga: 0–0.0050% by mass.
Citation Information
Patent Citations
JP1976013469B2
Manufacture of oriented electrical steel sheet by continuous casting method
JP1979031024A
Hot rolling method for one directional oriented silicon steel sheet
JP1980062124A
Aerating device for storage pond
JP1983024397A
Hot rolling method of anisotropic silicon steel plate
JP1985145204A